Load-Balanced Secure Routing Protocol for Wireless Sensor Networks - Wang Xin-sheng; Zhan Yong-zhao; Wang Liang-min (International Journal of Distributed Sensor Networks)
To solve the problems of limited energy of the nodes and security of routing in wireless sensor networks, load-balanced secure routing protocol (LSRP), a load-balanced secure routing protocol for wireless sensor networks, is proposed. Based on structured topology of hexagonal mesh, hops at different directions are calculated on the optimal route for transmitting data packets in LSRP. Depending on characters of hops, the nodes can rapidly find a route among multiple optimal routes by the policy of the twice probability routing selection. Data breach is prevented by data encryption, and data security is realized by one-way hash key chain and symmetric key authentication. LSRP offers preventions against usual attacks, and it also takes into account traffic load balance. Analysis and simulation results show that LSRP has better performance on traffic load balance and security.